2012
DOI: 10.5830/cvja-2012-036
|View full text |Cite
|
Sign up to set email alerts
|

Different lipid profiles according to ethnicity in the Heart of Soweto study cohort of de novo presentations of heart disease : cardiovascular topics

Abstract: BackgroundHistorically, sub-Saharan Africa has reported low levels of atherosclerotic cardiovascular disease (CVD). However as these populations undergo epidemiological transition, this may change.MethodsThis was an observational cohort study performed at Chris Hani Baragwanath Hospital in Soweto, South Africa. As part of the Heart of Soweto study, a clinical registry captured detailed clinical data on all de novo cases of structural and functional heart disease presenting to the Cardiology unit during the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
22
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 22 publications
10
22
1
Order By: Relevance
“…However, it is more likely that ethnic differences in the relationships between the LPL X and CETP B2 allele and serum lipid levels are due to differences in lifestyle factors between black and white SA women, specifically the intake of dietary fat [6,7,41]. We have previously shown that black women consume more energy, particularly as dietary fat, than white women [26,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is more likely that ethnic differences in the relationships between the LPL X and CETP B2 allele and serum lipid levels are due to differences in lifestyle factors between black and white SA women, specifically the intake of dietary fat [6,7,41]. We have previously shown that black women consume more energy, particularly as dietary fat, than white women [26,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…However in the USA, it has been reported that HDL-C levels are higher in black compared to white women [4,5], whereas in SA, HDL-C levels are similar or lower in black compared to white women [3,6,7]. These observations could explain why black SA women have a lower cholesterol-attributed mortality rate (47 in 100 000) compared to white women (152 in 100 000) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension was equally prevalent among men and women in this population, while hypercholesterolemia was relatively low in this population. This may not be unconnected with the fact that Africans are known to have low cholesterol for genetic reasons (Sliwa et al, 2012;Bentley and Rotimi, 2017). The occurrence of the CVD risk factors in this study increased with age.…”
Section: Prevalence Of Cvd Risk Factorsmentioning
confidence: 54%
“…(Table 1) In the Heart of Soweto study, Black African patients had significantly lower total-cholesterol, LDLcholesterol and triglycerides compared with Indian, White and mixed ethnic groups; however, HDL-C did not differ between ethnic groups. 6 Similarly in 2001, Punyadeera et al showed that South African White women presented with higher total cholesterol, triglycerides and LDLcholesterol concentrations than Black women, but HDL-C concentrations did not differ by ethnicity. tions than matched African diabetic patients, most likely due to access to statin therapy, which is available in more developed countries.…”
Section: 25mentioning
confidence: 97%
“…[1][2][3] Progressive changes in socioeconomic status and a Westernized lifestyle contribute to the burden of preventable CVD. [4][5][6] Since first demonstrated in the Framingham Heart study, it is now generally accepted that high-density lipoprotein cholesterol levels (HDL-C) are inversely correlated with CVD risk. [7][8][9] Much of the benefits of HDL are thought to be related to its antiatherogenic functions including reverse cholesterol efflux, anti-oxidative, anti-inflammatory and anti-thrombotic properties.…”
Section: Introductionmentioning
confidence: 99%